Planning in educational administration. An example of the action plan of the High Inspection of Education - Esteban Frades, Santiago; María Nieves (Avances en Supervisión Educativa, 2022)
A reflection on the need for planning of the High Inspection in Spain is presented and a proposal for an action plan for the High Inspection of Education in Castilla y León is developed. To do this, a historical review of the planning decisions made by educational administrations, educational centres, teachers and the educational inspection is carried out.
Keywords: High inspection; planning; educational administration; action plan